2006
DOI: 10.1152/ajpregu.00808.2005
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide and prostaglandins influence local skeletal muscle blood flow during exercise in humans: coupling between local substrate uptake and blood flow

Abstract: Synergic action of nitric oxide (NO) and prostaglandins (PG) in the regulation of muscle blood flow during exercise has been demonstrated. In the present study, we investigated whether these vasodilators also regulate local blood flow, flow heterogeneity, and glucose uptake within the exercising skeletal muscle. Skeletal muscle blood flow was measured in seven healthy young men using near-infrared spectroscopy and indocyanine green and muscle glucose uptake using positron emission tomography and 2-fluoro-2-deo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
21
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 62 publications
2
21
0
Order By: Relevance
“…[91][92][93][94][95][96][97][98] These transmitters also play a role in the adjustments of energy metabolism to muscle contractions (figure 4). [99][100][101][102][103][104][105] Because the effects of kinins are attenuated by inhibitors of the three enzymes mentioned above, causing diminished concentrations of downstream factors, [106][107][108][109][110] it has been postulated that kinins signal through NO, prostaglandins, and EDHF. 78 The molecular mode of action of these mediators has been described in detail by others.…”
Section: O P Y R I G H T J R a A S L I M I T E D R E P R O D U C T mentioning
confidence: 99%
See 2 more Smart Citations
“…[91][92][93][94][95][96][97][98] These transmitters also play a role in the adjustments of energy metabolism to muscle contractions (figure 4). [99][100][101][102][103][104][105] Because the effects of kinins are attenuated by inhibitors of the three enzymes mentioned above, causing diminished concentrations of downstream factors, [106][107][108][109][110] it has been postulated that kinins signal through NO, prostaglandins, and EDHF. 78 The molecular mode of action of these mediators has been described in detail by others.…”
Section: O P Y R I G H T J R a A S L I M I T E D R E P R O D U C T mentioning
confidence: 99%
“…76,120 Prostaglandins, such as PGE 2 and PGI 2 , may also participate in the control of vasodilation in SMT. 7,102,103,105 Prostaglandins are formed and released during contractions in the venous effluent. Their concentrations increase in the intercellular space, and they contribute to contraction-induced vasodilation in humans.…”
Section: O P Y R I G H T J R a A S L I M I T E D R E P R O D U C T mentioning
confidence: 99%
See 1 more Smart Citation
“…Nitric oxide [NO; synthesized via nitric oxide synthase (NOS)] and vasodilating prostaglandins [PGs; synthesized via cyclooxygenase (COX)] are two endothelium-derived vasodilatory substances that contribute to the hyperemic response during dynamic knee-extensor exercise in young healthy humans (1,14,21,22). In the forearm model, combined inhibition of NO and PG synthesis during exercise in young adults results in a significant decrease in forearm blood flow (FBF; ϳ20%), primarily mediated through NOS inhibition (30).…”
mentioning
confidence: 99%
“…Some animal studies have subsequently found evidence that NO tonically inhibits mitochondrial respiration in vivo (33-35), but there has not been evidence for this in humans (10,27,31). It is well shown with various methods that prostanoids can act synergistically with NO to regulate vascular function in health and disease (2,19,23,30,31), but COX inhibition may also have direct effects on cellular aerobic respiration by affecting uncoupling (17,20,23).Positron emission tomography (PET) is a noninvasive imaging method based on short-lived radioisotopes that can be applied to measure blood flow and its distribution in muscle. Muscle blood flow by PET can be quantified with [ 15 O]H 2 O (radiowater), which is an intravenously infused inert and freely diffusible tracer.…”
mentioning
confidence: 99%